1999
DOI: 10.1126/science.283.5401.516
|View full text |Cite
|
Sign up to set email alerts
|

An ~15,000-Year Record of El Niño-Driven Alluviation in Southwestern Ecuador

Abstract: Debris flows have deposited inorganic laminae in an alpine lake that is 75 kilometers east of the Pacific Ocean, in Ecuador. These storm-induced events were dated by radiocarbon, and the age of laminae that are less than 200 years old matches the historic record of El Nino events. From about 15,000 to about 7000 calendar years before the present, the periodicity of clastic deposition is greater than or equal to 15 years; thereafter, there is a progressive increase in frequency to periodicities of 2 to 8.5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
432
3
15

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 691 publications
(502 citation statements)
references
References 30 publications
40
432
3
15
Order By: Relevance
“…Inasmuch as the Holocene section of most cores is a dark gyttja with 15-20 wt.% organic C, the light-gray tephras are distinct. However, some cores contain a complex sequence of thin laminae of gyttja alternating with light-colored inorganic clastic sediment, such as the core from Laguna Pallcacocha (Rodbell et al,1999). In these cases, tephras were identified through the inspection of smear slides and confirmation of the presence of angular and vesicular glass shards and phenocrysts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inasmuch as the Holocene section of most cores is a dark gyttja with 15-20 wt.% organic C, the light-gray tephras are distinct. However, some cores contain a complex sequence of thin laminae of gyttja alternating with light-colored inorganic clastic sediment, such as the core from Laguna Pallcacocha (Rodbell et al,1999). In these cases, tephras were identified through the inspection of smear slides and confirmation of the presence of angular and vesicular glass shards and phenocrysts.…”
Section: Methodsmentioning
confidence: 99%
“…Because Laguna Pallcacocha is well dated (Rodbell et al, 1999), most tephra age assignments are based on correlation to this core. In addition, basal dates were also obtained from each core and all well-preserved terrestrial macrofossils found in the other cores were also dated (Bagnato, 2000); these dates were also used in developing the tephrochronology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of the Holocene is characterised by a weakening and reduction of amplitude of the ENSO (Moy et al, 2002;Rodbell et al, 1999). The establishment of a long-term La Niña pattern in the tropical Pacific during this period seems to be a consequence of the ENSO activity reduction (Hernández et al, 2010;Koutavas et al, 2002).…”
Section: Geology Limnology and Climatementioning
confidence: 99%
“…and a more La-Niña-like average state, a condition correlated with drier winter conditions in the Southwest (e.g. Rodbell et al, 1999;Clement et al, 2000). With the onset of greater ENSO frequency and magnitude in the later part of the midHolocene, the southwestern United States would have experienced more regular winter precipitation with greater extremes (Cane, 2005) and possibly higher freezing level heights, i.e., the elevation above sea level at which the air temperature is close to 0˚C (Diaz et al, 2003).…”
Section: Mid-to Late Holocenementioning
confidence: 99%